Achondroplasia: aligning mouse model with human clinical studies shows crucial importance of immediate postnatal start of the therapy - Rico-Llanos, Gustavo; Spoutil, Frantisek; Blahova, Eva; Koudelka, Adolf; Prochazkova, Michaela; Czyrek, Aleksandra; Fafilek, Bohumil; Prochazka, Jan; Gonzalez Lopez, Marcos; Krivanek, Jan; Sedlacek, Radislav; Krakow, Deborah; et al. (Journal of bone and mineral research, 2024)
Achondroplasia is the most common form of human dwarfism caused by mutations in the FGFR3 receptor tyrosine kinase. Current therapy begins at 2 years of age and improves longitudinal growth but does not address the cranial malformations including midface hypoplasia and foramen magnum stenosis, which lead to significant otolaryngeal and neurologic compromise. A recent clinical trial found partial restoration of cranial defects with therapy starting at 3 months of age, but results are still inconclusive. The benefits of achondroplasia therapy are therefore controversial, increasing skepticism among the medical community and patients. We used a mouse model of achondroplasia to test treatment protocols aligned with human studies. Early postnatal treatment (from day 1) was compared with late postnatal treatment (from day 4, equivalent to ~5 months in humans). Animals were treated with the FGFR3 inhibitor infigratinib and the effect on skeleton was thoroughly examined. We show that premature fusion of the skull base synchondroses occurs immediately after birth and leads to defective cranial development and foramen magnum stenosis in the mouse model to achondroplasia. This phenotype appears significantly restored by early infigratinib administration when compared with late treatment, which provides weak to no rescue. In contrast, the long bone growth is similarly improved by both early and late protocols. We provide clear evidence that immediate postnatal therapy is critical for normalization of skeletal growth in both the cranial base and long bones and the prevention of sequelae associated with achondroplasia. We also describe the limitations of early postnatal therapy, providing a paradigm-shifting argument for the development of prenatal therapy for achondroplasia.
Keywords: Receptor, Fibroblast Growth Factor, Type 3; myši; Disease Models, Animal; lebka; Skull; modely nemocí na zvířatech; zvířata; achondroplazie; Humans; Achondroplasia; Mice; receptor fibroblastových růstových faktorů, typ 3; lidé; Animals